1998
DOI: 10.1029/98wr01922
|View full text |Cite
|
Sign up to set email alerts
|

open‐channel flow through simulated vegetation: Suspended sediment transport modeling

Abstract: The present work aims at using a turbulence closure scheme to model suspended sediment transport processes in freesurface flows through vegetation and at evaluating the influence of different flow, sediment, and plant properties on the capacity of these systems to transport sediment as suspended load. Dimensional AnalysisThe investigation of sediment transport processes in vegetated channels involves the consideration of such a large set of variables characterizing the sediment, flow and plants properties, tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
168
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(172 citation statements)
references
References 9 publications
2
168
0
2
Order By: Relevance
“…It has long been held that vegetated zones promote particle removal by enhancing residence time (Knight et al 1999) and reducing resuspension (Lopez and Garcia 1998). Indeed, Gacia et al (1999) observed that retention of particles by a seagrass meadow is up to 15 times greater than by barren beds.…”
mentioning
confidence: 99%
“…It has long been held that vegetated zones promote particle removal by enhancing residence time (Knight et al 1999) and reducing resuspension (Lopez and Garcia 1998). Indeed, Gacia et al (1999) observed that retention of particles by a seagrass meadow is up to 15 times greater than by barren beds.…”
mentioning
confidence: 99%
“…It acts as an additional source of channel resistance and has been shown to alter bulk flow velocities and conveyance [2][3][4], generate turbulence through coherent flow structures [5][6][7][8], modify sediment transport processes [9][10][11] and increase habitat diversity [12,13]. Therefore, a good process understanding of boundary layer flow through and around vegetation is central in predicting the functioning of the fluvial system.…”
Section: Introductionmentioning
confidence: 99%
“…For regularly-arrayed plants , because the extent of the averaging plane of scheme I is much larger than in scheme II, it can be obtained that <ui>=<ui> and <p>=<p> (Lopez and Garcia 1997). Thus, from Eqs .…”
Section: Averaging Schemesmentioning
confidence: 95%
“…The Reynolds stresses due to spatially fluctuating velocities, < uiuj> , have not been measured so far , so that their relative effect upon the total stress remains still unknown (Lopez and Garcia 1997). If we assume that the flow is steady and fully-developed, then the averaged momentum equation is given by…”
Section: Averaging Schemesmentioning
confidence: 99%